Physiological and transcriptomic analyses of exogenous calcium in boosting nitrogen use efficiency via oxidative and resistance pathways in peanuts - Xu, Fengdan; Li, Liang; Si, Xianzong; Suo, Yanyan; Wang, Xiaolin; Zhang, Zhehui; Li, Qian; Zhang, Xiang (Frontiers in Plant Science, 2026)
IntroductionPeanuts (Arachis hypogaea L.) exhibit a high demand for calcium, second only to nitrogen and potassium, with calcium playing a critical role in their growth, development, and nitrogen fixation. However, the mechanisms underlying calcium-mediated regulation of peanut growth and nitrogen fixation remain poorly understood. MethodsIn this study, we employed nitrogen-efficient (Puhua 66, Huayu 20) and nitrogen-inefficient (Puhua 28, Shanhua 14) peanut varieties in a two-year field experiment using a split-plot design. The main plots comprised two treatments: standard fertilization (CK) and calcium supplementation (Ca), while the sub-plots consisted of different peanut varieties. We analyzed growth parameters, physiological responses, and transcriptomic profiles.ResultsOur results demonstrated that calcium application significantly increased malondialdehyde (MDA) content in leaves while reducing peroxidase (POD) activity, enhancing pod dry matter accumulation, and promoting earlier plant maturation. Additionally, calcium application elevated the activities of nitrate reductase (NR) and glutamine synthetase (GS) (P < 0.01), thereby improving nitrogen and calcium accumulation in pods, their allocation efficiency, and the overall utilization rates of nitrogen and calcium fertilizers. Transcriptomic analysis revealed 166 differentially expressed genes (DEGs) in nitrogen-efficient varieties and 343 DEGs in nitrogen-inefficient varieties under calcium supplementation, with 67 DEGs shared between the two groups. Functional annotation and qRT-PCR validation were performed on these DEGs.Furthermore, weighted gene co-expression network analysis (WGCNA) indicated that calcium supplementation significantly up-regulated genes associated with sucrose synthase, β-amylase, GTPase-activating proteins, light-harvesting chlorophyll-protein complexes (Lhca2, Lhca3), photosynthetic electron transport (PetF, PetJ), phosphatidylinositol phospholipase C2, inositol-3-phosphate synthase, TMV resistance protein, ABC transporters, ethylene-responsive transcription factors (EIN1, EIN2, EIN3), alkylamine oxidase, glutamate dehydrogenase, and aspartate synthase.ConclusionThese findings suggest that calcium application modulates carbohydrate metabolism, nitrogen assimilation, plant-pathogen interactions, and photosynthetic processes through differential gene expression, ultimately enhancing leaf physiological activity, dry matter partitioning, pod yield, and early maturation in peanuts.